The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.strusafe.2015.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

An empirical comparison of machine learning techniques for dam behaviour modelling

Abstract: Predictive models are essential in dam safety assessment. Both deterministic and statistical models applied in the day-to-day practice have demonstrated to be useful, although they show relevant limitations at the same time. On another note, powerful learning algorithms have been developed in the field of machine learning (ML), which have been applied to solve practical problems. The work aims at testing the prediction capability of some state-of-the-art algorithms to model dam behaviour, in terms of displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(98 citation statements)
references
References 16 publications
0
98
0
Order By: Relevance
“…The authors found that models with relatively high ARV corresponded with very low M AE, close to the measurement error [58].…”
Section: Mean Squared Errormentioning
confidence: 70%
See 3 more Smart Citations
“…The authors found that models with relatively high ARV corresponded with very low M AE, close to the measurement error [58].…”
Section: Mean Squared Errormentioning
confidence: 70%
“…The authors [58] performed a comparative study among various statistical and ML methods, including HST, NN, and others which had been never used before in dam monitoring, such as random forests (RF) or boosted regression trees (BRT). It was reported that innovative ML algorithms offered the most accurate results, although no one performed better for all 14 outputs analysed, which corresponded to radial and tangential displacements and leakage flow in an arch dam.…”
Section: Other ML Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in actual practice, approaches like Scheme 3 might be also preferable if a conservative prediction is of interest. (Mirzavand et al 2015), dam behavior (Salazar et al 2015), coal pillar stability (Zhou et al 2015), slope stability (Suman et al 2016), and rock burst hazards (Zhou et al 2016a). 6.2 Selection of parameters and model construction (Goel and Singh 2011) and it is therefore often unavailable at early stages of one project; (ii) actual measurements of tunnel support pressure are unavailable until the support is constructed, and their prior estimations are often unfeasible, as suggested by the large discrepancies found between estimations and measurements in real cases (Bhasin and Grimstad 1996); and (iii) the ranges of variability of rock mass unit weights are often limited, so that they can often be assumed constant in this type of practical empirical prediction (Dwivedi et al 2013). …”
Section: Discussionmentioning
confidence: 99%